Zakaz amortyzacji lokali mieszkalnych z perspektywy konstytucyjno prawnej. Uwagi na tle obecnego dorobku sądów administracyjnych - Skwirowska, Justyna (PRAWO i WIĘŹ, 2025)
One of the newly introduced provisions along with the so-called „Polish Deal” was a complete ban on depreciation of residential premises. At the same time, both taxpayers and representatives of the literature questioned its compliance with constitutional principles, i.e. the principle of protection of vested rights and the principle of protection of pending interests. Taxpayers raised the issue of the unconstitutionality of this regulation and applied for individual interpretations. The unfavourable positions of the Director of National Tax Information led to disputes before administrative courts. The juries that decided these cases also did not agree with the plaintiffs’ arguments. The purpose of this paper is to examine the legitimacy of these decisions and to consider whether the ban is in fact incompatible with the Polish Constitution.